Dead again [videorecording (Blu-Ray)] - Branagh, Kenneth; Frank, Scott, 1960-; Thompson, Emma; Williams, Robin, 1951-2014; Garcia, Andy (KL studio classics., 2026)
Mike Church is an L.A. gumshoe with a knack for tossing off wisecracks and tracking down missing people. But Church doesn't have a clue when he's hired to help a beautiful amnesia victim tormented by blood-curdling nightmares. Then an eccentric antiques dealer and hypnotist leads Church to a startling discovery: The source of the nightmares may lie in a past-life connection to Margaret Strauss, a world-famous pianist allegedly murdered by her composer husband...in 1948.